Enhancing therapeutic effects of murine cancer vaccine by reshaping gut microbiota with Lactobacillus rhamnosus GG and jujube powder - Jing, Nan; Wang, Luoyang; Zhuang, Huiren; Jiang, Guoqiang; Liu, Zheng (Frontiers in Immunology, 2023)
Cancer vaccines have gained widespread attention in recent years as an emerging treatment for tumors. However, most therapeutic cancer vaccines have failed in phase III clinical trials due to faint clinical benefits. In this study, we funded that a specific synbiotic composing Lactobacillus rhamnosus GG (LGG) and jujube powder significantly enhanced the therapeutic effects of whole cells cancer vaccine in MC38 cancer cells bearing-mouse. The utilization of LGG increased the abundance of Muribaculaceae, which is conductive to an enhanced anti-tumor effect, but reduced microbial α-diversity. The use of jujube nursed probiotic microorganisms in Lachnospiaceae and enriched microbial diversity, as indicated by increased Shannon and Chao index. The reshaped gut microbiota by this synbiotic improved lipid metabolism conductive to intensified infiltration of CD8+ T cells in the tumor microenvironment and enhanced the potency of above-mentioned cancer vaccine. These encouraging findings are helpful for further efforts towards enhancing the therapeutic effects of cancer vaccines through nutritional intervention.